On Heidegger's Nazism and philosophy - Rockmore, Tom 1942- (Univ. of California Press, 1992)
That Martin Heidegger supported National Socialism has long been common knowledge. Yet the relation between his philosophy and political commitments remains highly contentious and recently has erupted into a vociferous debate. Boldly refuting arguments that the philosopher's political stance was accidental or adopted under coercion, Rockmore argues that Heidegger's philosophical thought and his Nazism are inseparably intertwined, that he turned to National Socialism on the basis of his philosophy, and that his later evolution is largely determined by his continuing concern with Nazism